Practical guide to respirator usage in industry. - Rajhans, Gyan S
This new edition outlines the design and implementation of an effective respiratory protective equipment program for industries in which workers are at risk from inhaled particulates, toxins and other hazardous materials. The book is intended for managers, health and safety committees, safety specialists and occupational health professionals who need the most up-to-date and practical advice in a concise and easy to read step-by-step form rather than an abstract and theoretical reference on the subject.As in the first edition, the authors present individual components of a respiratory protectio.